Study on Chemical Components and Antioxidant Activity of Cream Products Made of Telang Flower (Clitoria ternatea L.) and Honey - Sahira Josy Arifannisa; Dewi Sartika; Sussi Astuti; Tanto Pratondo Utomo; Suharyono Suharyono (The University of Lampung, 2025)
Facial skin is most often exposed to UV rays and various disorders that need special creams with active ingredients containing antioxidant properties. This study aims to determine the chemical compounds of butterfly pea or telang flower (Clitoria ternatea L.) and determine the antioxidant activity of its cream products. Six treatments consisted of ratio flower extract to honey were performed. The chemical components of telang flower were determined by GCMS method and antioxidant activity test using DPPH method. Results showed that major compound with retention at 23.989; 27.039; and 27.641 min were hexadecanoic acid, oleic acid, and octadecanoic acid with area percentage of 32.70%; 28.92%; and 15.42%, respectively. In addition, there were 5 minor compounds including palmitoyl chloride with retention 28.710 min and area of 7.07%, glycidyl palmitate (retention 18.767 min, area of 5.76%), Heptacosanol (retention 22.818 min, area of 3.01%), Nitroisobutylglycerol (retention 18.059 min, area of 4.50%), and Hydroxymethylfurfural (retention 14.324 min, area of 2.61%). Based on the antioxidant activity test, the highest antioxidant activity results were found in cream formulation 1 (F1) with an IC50 of 3.906 μg/mL, followed by cream formulation 2 (F2) which has antioxidant activity after of 6.532 μg/mL. Keywords: Antioxidant activity, Telang flower, DPPH, GCMS, Honey.